Zacátky Ceské chirurgické spolecnosti - Sváb, J; Vecerníková, J (Rozhledy v chirurgii, 1995)
The authors present a brief of the position of Czech Surgery in medicine during the last century. They mention the conditions for association of the Czech doctors in the second half of the 19th century as a manifestation of national revival efforts. In 1860 the Czech Medical Society was founded and in 1862 the first issue of the Czech Medical Journal was published. The climax of Czech desires of revival was the separation of Czech and German clinics in 1883. The development of some medical disciplines, incl. surgical disciplines, made the surgeons abandon the Czech Medical Society and after the establishment of the committee of the Czechoslovak Republic they founded in 1920 the committee of the Czechoslovak Society for Surgery and Gynaecology. In April 1921 the first congress of the Czechoslovak Surgical and Gynaecological Society was held. At this occasion the first issue of the Surgical and Gynaecological Review (Rozhledy v chirurgii a gynaekologii) was published. Both events laid the foundations of the contemporary Czech Society of Surgeons.
Keywords: General Surgery; chirurgie; Societies, Medical; dějiny 19. století; History, 20th Century; dějiny 18. století; společnosti lékařské; Czech Republic; History, 18th Century; dějiny 20. století; History, 19th Century; Česká republika